Penerapan Lean Manufacturing untuk Meminimasi Proses Dandori Mesin Molding Pada PT XYZ dengan Metode SMED - Raihan Rahmadianto; Mega Cattleya PA Islami (Jurnal Kendali Teknik dan Sains, 2024)
PT XYZ is a manufacturing company that produces various products, such as molds and several spare parts. The production process often experiences wasted time at the machine setup stage, known as dandori. To avoid production delays, companies need to increase their productivity. This research aims to propose the application of Lean Manufacturing methods, especially SMED, to reduce machine uptime by focusing on optimizing external activities in mold making. Through the application of the Single Minute Exchange of Dies (SMED) concept, fourteen internal activities were changed to eight internal activities, resulting in improvements with a reduction in machine setup time from 44 minutes to 22 minutes, or a reduction of 50%. The hope is that these results will increase the company's output significantly.